A Comparison of Four Digital Otoscopes in a Teleconsultation Setting. (31st October 2019) - Tötterman, Magnus; Jukarainen, Sakari; Sinkkonen, Saku T.; Klockars, Tuomas
Abstract : Objectives/Hypothesis: This study compares image quality and appropriateness for teleconsultations for three different otological conditions. Study Design: Web‐based survey. Methods: We compared four digital otoscopes via a Web‐based questionnaire distributed to all Finnish ear, nose, and throat (ENT) specialists and residents. The survey consisted of three fictional patient cases, each of which was presented with images taken using the otoscopes studied. Respondents assessed the image quality on a visual analog scale (VAS), assessing its appropriateness for teleconsultations and comparing images taken using different otoscopes to one another. Results: In total, 98 individuals responded, consisting of 81 ENT specialists and 17 ENT residents. The CellScope Oto and Digital MacroView received higher VAS scores for image quality and appropriateness for teleconsultations than the FireFly and Delfino otoscopes ( P < .001 for all comparisons). Respondents considered the CellScope Oto more appropriate for teleconsultations for exostoses than the three other otoscopes. The CellScope Oto and Digital MacroView were equally appropriate in the two other cases (normal ear and perforated tympanic membrane). Conclusions: Both digital otoscopes and the underlying otological conditions affect the appropriateness of teleconsultations. Moreover, both factors should be considered when evaluating the suitability of otologic teleconsultations. Among the otoscopes evaluated, images taken using the CellScope Oto received the best overall assessments. Level of Evidence: NA Laryngoscope, 130:1572–1576, 2020